PENGARUH KONFLIK INTERNAL PARTAI POLITIK DALAM PENGUSULAN PIMPINAN DPRD BAGI PENYELENGGARAN PEMERINTAHAN DAERAH ( Studi Terhadap Disparitas Pegusulan Ketua DPRD Kayong Utara) - ALHUSAINI. SH. A.2021141078, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis focuses on the influence of political parties in the internal conflict of the nomination of the leadership of Parliament for the regional administration. From the study authors using normative juridical research method, the conclusion: that 1). Construction is contained in article 164 and article 165 of Law No. 23 Year 2014 on Regional Government only administratively wrote. Within the meaning of these articles only regulate how to determine candidates for the leadership of Parliament on condition that the vote general election results obtained by each political party. The most votes storied be decisive to occupy the leadership of Parliament. Then the solution is regulated in Law No. 2 of 2008 on Political Parties as amended by Law No. 2 of 2011 if there is a conflict in the internal political party that is completed by the political parties themselves by basing on the Statutes and Bylaws and as institution resolving disputes internal conflicts of political parties was submitted to the Court a party formed by the political parties themselves. If the matter is not resolved by the Court Party, the Institute for Court becomes the exit to resolve the internal conflict of the political party. 2) internal .konflik particular political party to propose and determine the leadership of Parliament directly or indirectly influence in local governance. This is due to Parliament is a partner of the local government and at the same as the regional administration. Furthermore, of the rights and duties and the authority of the parliament and then accelerated to the rights and the duties and authority of the head of the region, then there is a very close working relationship in governance in the region. Every action and authority possessed by the head of the region has always been linked to parliament, both in order to give consideration and approval. The relationship of labor and employment partner at the same time, the institution of Parliament concerning the status of members and leaders should have any legal standing or position that has been legalized. If the leadership of Parliament is not yet definitive, all the regional administration will stagnate because of the institutional, Parliament does not have the leadership. Leader while Parliament is generally only serves to organize and carry out in the framework of a definitive determination of the leadership of Parliament. 3). In the law of political parties No. 2 of 2008 as amended by Law No. 2 of 2011 that the mechanisms for resolving conflicts of political parties can be completed with two (2) ways namely through Supreme Party or other designations established by the political party concerned and agencies pengadilan.Di outside of legislation governing political parties in the conflict resolution, Nasikun provide a model on the settlement of the conflict. There is also an offer from Nasikun in conflict resolution are: conciliation, mediation, abitrase and perwasian. But the writer believes there are only two (2) models that can be used to resolve internal conflicts of political parties namely conciliation and mediation. The suggestions are: 1). political parties in determining the leadership of Parliament do not be concerned with the interests of individuals or groups because the longer the old parties of political parties propose and determine the leadership of Parliament, it can affect the head of administration of blood. 2) .had no revisions back to the law of political parties by entering the model or form or other means other than the Party and resolved by the Supreme Court Institute, that political party's internal conflict resolution can be solved in an easy manner and did not take long.2ABSTRAKTesis ini menitikberatkan pada pengaruh konflik internal partai politik dalam pengusulan pimpinan DPRD bagi penyelenggaraan pemerintahan daerah. Dari penelitian penulis dengan menggunakan metode penelitian yuridis normatif, diperoleh kesimpulan: bahwa 1). Konstruksi yang terdapat dalam pasal 164 dan pasal 165 Undang Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah hanya bersifat administratif aja. Dalam arti pasal-pasal tersebut hanya mengatur bagaimana menentukan calon pimpinan DPRD dengan syarat perolehan suara hasil pemilhan umum yang diperoleh oleh masing-masing partai politik. Suara terbanyak secara bertingkat menjadi penentu untuk menduduki pimpinan DPRD. Kemudian solusi yang diatur dalam Undang Undang No 2 Tahun 2008 Tentang Partai Politik sebagaimana telah di ubah dengan Undang Undang Nomor 2 Tahun 2011 jika terjadi konflik dalam internal partai politik yakni diselesaikan oleh partai politik itu sendiri dengan mendasarkan pada Anggaran Dasar dan Anggaran Rumah Tangga dan sebagai lembaga pemutus atas sengketa konflik internal partai politik tersebut diserahkan pada Mahkamah Partai yang dibentuk oleh partai politik itu sendiri. Jika pun tidak terselesaikan oleh Mahkamah Partai, maka Lembaga Pengadilan menjadi pintu keluar untuk menyelesaikan konflik internal partai politik tersebut. 2).konflik internal partai politik khususnya untuk mengusulkan dan menentukan pimpinan DPRD secara langsung atau tidak langsung berpengaruh dalam penyelenggaraan pemerintahan daerah. Hal ini disebabkan DPRD merupakan mitra kerja dari pemerintah daerah dan sama sama sebagai penyelenggara pemerintahan daerah. Selanjutnya dari hak-hak serta tugas dan wewenang yang dimiliki oleh DPRD dan kemudian diakselerasikan dengan hak-hak serta tugas dan wewenang kepala daerah, maka terdapat hubungan kerja yang sangat erat dalam penyelenggaraan pemerintahan di daerah. Setiap tindakan dan kewenangan yang dimiliki oleh kepala daerah selalu terkait juga dengan DPRD, baik dalam rangka memberikan pertimbangan maupun persetujuan. Keeratan hubungan kerja dan sekaligus mitra kerja, maka kelembagaan DPRD menyangkut status anggota dan pimpinan harus mempunyai legal standing atau kedudukan yang telah di sahkan. Apabila pimpinan DPRD belum bersifat definif, maka segala penyelenggaraan pemerintahan daerah akan stagnan karena secara kelembagaan, DPRD belum mempunyai pimpinan. Pimpinan sementara DPRD secara umum hanya berfungsi untuk mengatur dan melaksanakan dalam rangka penetapan pimpinan DPRD definitif. 3). Di dalam undang undang partai politik nomor 2 tahun 2008 sebagaimana telah diubah dengan Undang Undang Nomor 2 Tahun 2011 bahwa mekanisme penyelesaian konflik partai politik dapat diselesaikan dengan 2 (dua) cara yakni melalui Mahkamah Partai atau sebutan lain yang dibentuk oleh partai politik yang bersangkutan serta lembaga pengadilan.Di luar dari peraturan perundang-undangan yang mengatur dalam penyelesaian konflik partai politik, Nasikun memberikan model terhadap penyelesaian konflik. Ada pun tawaran dari Nasikun dalam penyelesaian konflik adalah : konsiliasi, mediasi,abitrase dan perwasian. Akan tetapi penulis berpendapat hanya terdapat 2 (dua) model saja yang dapat dipergunakan untuk menyelesaikan konflik internal partai politik yakni konsiliasi dan mediasi. Saran-saran adalah : 1). partai politik dalam menentukan pimpinan DPRD jangan mementingkan kepentingan perorangan atau golongan karena semakin lama partai lama partai politik mengusulkan dan menentukan pimpinan DPRD maka dapat berpengaruh kepala penyelenggaraan pemerintahan darah. 2).harus ada revisi kembali terhadap undang-undang partai politik dengan memasukkan model atau bentuk atau cara lain selain diselesaikan oleh Mahkamah Partai dan Lembaga Pengadilan, agar penyelesaian konflik internal partai politik dapat diselesaikan dengan cara yang mudah serta tidak memakan waktu yang cukup lama.